Design and Fabrication of Horizontal Axis Wind Turbine - Mula Pavan Kumar Reddy; Hanumanthe Gowda; Nalina L; Kariyanna Gari Shashank; Prabhu G V (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
We Know that there exists a significant wind potential worldwide that could potentially fulfill a substantial portion, if not the majority, of humanity’s energy needs if harnessed efficiently and at scale. By enhancing the efficiency of wind turbines, we can generate more power, thereby reducing reliance on costly and polluting conventional power sources. This project aims to design an experimental setup for Horizontal Axis Wind Turbines (HAWTs), which present practical, straightforward, and cost-efficient alternatives to existing systems. One key advantage is their ability to capture wind from all directions.